Development of a retroviral strategy that efficiently creates nested chromosomal deletions in mouse embryonic stem cells and its exploitation for functional genomics - Bilodeau, Mélanie (2016)
Thèse numérisée par la Direction des bibliothèques de l'Université de Montréal.